Strategi pembangunan ekonomi daerah berbasis pemetaan sektor unggulan: Analisis LQ, DLQ, dan tipologi klassen di Kabupaten Tanah Bumbu - La Ode Muhammad Iksan Yusuf; Regina Regina; Irwandi Irwandi; Arsianita Nur Fattah; Sarinah Sarinah (Nur Science Institute, 2026)
This study aims to identify leading and prospective economic sectors and analyze their positions within the economic structure of Tanah Bumbu Regency, using Gross Regional Domestic Product (GRDP) data for 2020–2024. The analytical methods used include the Location Quotient (LQ), the Dynamic Location Quotient (DLQ), and the Klassen Typology. The results show that the agriculture, forestry, and fisheries sectors, as well as mining and quarrying, are basic sectors with LQ values> 1, indicating comparative advantage and significant contributions to the regional economy. DLQ analysis identifies six sectors with growth prospects: agriculture, mining, manufacturing, electricity and gas procurement, information and communication, and government administration. Meanwhile, the trade, construction, and transportation sectors show relatively low growth prospects. Based on the Klassen Typology, the leading sectors are categorized as advanced and growing rapidly, while the other sectors are categorized as potentially developing or lagging. These findings form the basis for formulating more targeted and sustainable economic development policies.